2022
DOI: 10.1016/j.jmh.2022.100079
|View full text |Cite
|
Sign up to set email alerts
|

Testing strategies to contain COVID-19 in migrant worker dormitories

Abstract: Introduction COVID-19 transmission within overcrowded migrant worker dormitories is an ongoing global issue. Many countries have implemented extensive control measures to prevent the entire migrant worker population from becoming infected. Here, we explore case count outcomes when utilising lockdown and testing under different testing measures and transmissibility settings. Methods We built a mathematical model which estimates transmission across 10 different blocks wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Subsequently, 476 abstracts were reviewed, and 95 publications received a full-text review. Finally, 62 publications were included in the synthesis (the data-charting form is available in Multimedia Appendix 2 [ 20 - 46 ]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, 476 abstracts were reviewed, and 95 publications received a full-text review. Finally, 62 publications were included in the synthesis (the data-charting form is available in Multimedia Appendix 2 [ 20 - 46 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Baker et al [ 45 ] found that if the number of screening tests per day was slightly higher than the daily testing capacity, it would not cause a burden on testing, but more cases could be found and transmission could be reduced more effectively. Koo et al [ 46 ] assessed the impact of biweekly PCR tests or weekly RATs on the number of new infections and infectivity in areas with a high population density (such as workers’ dormitories) and found that biweekly PCR testing (39 new cases per month) was as effective as weekly RATs (33 new cases per month) and could prevent local outbreaks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation